The Measurement of Employee Performance Based on Work Stress and Workplace Conflict at BCA Finance Ltd Medan - Yoki Amriza; Husni Muharram Ritonga; Dewi Nurmasari Pane (Britain International for Academic Research (BIAR) Publisher, 2022)
Stress at work will cause various consequences for workers. Psychologically stress will cause a sense of job dissatisfaction with the emergence of emotional stress such as irritability, rudeness or anxiety (Warni, 2016). Conflict comes from the Latin verb